Indirect technique for estimating life expectancy from limited data set of BRAC female members - Gani, Md. Showkat; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2020)
This paper aims to construct the complete life table (L T) from limited data set of the female members of BRAC village organizations (VO) using the INDEPTH (International Network for the continuous Demographic Evaluation of Population and Their Health in developing countries) model life tables (MLT), and to justify the validity of the estimated results. The ML T technique was used to estimate the life expectancy of BRAC VO members because the data were available for women ranging from 18 - 55 years only. As a service to VO members, BRAC provides them insurance coverage against death. Secondary data set of BRAC female VO members was collected from the MIS of BRAC area level offices (sub-district level) and the insurance claims formed the main sources of data for this study. With a sample size of 186,379 women including 391 dead, the sampling design used was as follows: 12 of 45 BRAC district-level regions were randomly selected and 32 areas were again randomly selected from the selected regions. Using the INDEPTH ML T, a complete life table of BRAC female members was generated. The pattern of life expectancy curve of BRAC female VO members is similar to both the Matlab (a sub-district) and the national female population of Bangladesh. The closeness of life expectancy curves indicates that the technique used provided valid estimates. The life expectancy at birth of BRAC female members was estimated at 64 years in 1998, which was higher compared to national female population (61 years). The higher life expectancy among BRAC VO female members indicates that BRAC development interventions can be a catalytic agent in increasing the life expectancy among poor women in rural Bangladesh. Therefore, this demographic technique could be used for the indirect estimation of life table in developing countries of Asia and Africa.